Building Students' Spiritual Intelligence Through Holistic Learning In Faith Lessons - Ahmad Fajar Shodiq; Mukni’ah; Mustajab (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2025)
A dignified civilization of the nation can be formed through the national education system and related to the purpose of the education. For this reason, the implementation of the education system is focused on developing the potential of students which is carried out holistically, hence the need for education to strive for equity and growth of this latent potential so that the urgency of the implementation of holistic learning can be implemented in the existing education system. The purpose of this research is to analyze and describe the materials, methods and strategies of holistic learning in building spiritual intelligence in the lessons of the Akidah ahlak. This research method uses a qualitative method with a case study type. The location of this research is at the institution of Madrasah Aliyah Negeri 1 Jember. Data collection techniques are carried out through observation, interview and documentation techniques. Data analysis was carried out using the interactive technique of miles, huberman which includes data collection, data condensation, data presentation, and drawing conclusions or verification. The data validity technique is carried out using triangulation techniques. The results of the study indicate that in the subject matter holistically, the institution implements learning that is in accordance with the syllabus as it should be in terms of content and there is development through delivery by integrating with other cognate subject matter. Meanwhile, the lesson method combines various diverse learning methods including discussion, lecture, discovery, and question and answer methods. Then the lesson strategy is designed by creating students towards the individual as a whole through the application of the approach of example, observing and practicing or habituating